Scrub typhus in Indonesia: a cross-sectional analysis of archived fever studies samples - Saraswati, K; Tanganuchitcharnchai, A; Ongchaikupt, S; Mukaka, M; Day, NPJ; Baird, JK; Antonjaya, U; Myint, KSA; Dewi, YP; Yudhaputri, FA; Haryanto, S; Witari, NPD; et al. (Oxford University Press, 2024)
Background Scrub typhus is an understudied vector-borne bacterial infection. Methods We tested archived fever samples for scrub typhus seropositivity to begin charting its geographic distribution in Indonesia. We analysed 1033 serum samples from three sites. IgM and IgG enzyme-linked immunosorbent assay (ELISA) against Orientia tsutsugamushi was performed using Karp, Kato, Gilliam, TA 716 antigens. To determine the cutoff in the absence of a presumed unexposed population and gold standard tests, we identified the visual inflection point, performed change point analysis, and used finite mixture models. Results The optical density cutoff values used for IgM and IgG were 0.49 and 0.13, respectively. Across all sites, IgM seropositivity was 4.6% (95% CI: 3.4 to 6.0%) while IgG seropositivity was 4.4% (95% CI: 3.3 to 5.8%). The overall seropositivity across sites was 8.8% (95% CI: 8.1 to 11.7%). The overall seropositivity for Jambi, Denpasar, Tabanan were 9.7% (95% CI: 7.0 to 13.3%), 8.0% (95% CI: 5.7 to 11.0%), 9.0% (95% CI: 6.1 to 13.0%), respectively. Conclusions We conclude that O. tsutsugamushi exposure in humans occurred at all sites analysed and could be the cause of illness in some cases. Though it was not the main cause of acute fever in these locations, it is still important to consider scrub typhus in cases not responding to beta-lactam antibiotics. Future seroprevalence surveys and testing for scrub typhus in acute febrile illness studies will be essential to understand its distribution and burden in Indonesia.